Le temps vécu dans le récit de fiction et dans le récit historique (ENTHYMEMA, 2013)
Ricœur  evokes continuously the extraordinary resources offered by fiction to catch the subtle variants between the time of conscious and the chronological time, and finds the limits of history: compared to historical narrative, – writes Ricœur  - fiction narrative is richer in information on time, because of its powers of composition.